Structural and functional analysis of the related transcriptional enhancer factor-1 and NF-κB interaction - Ma, Jieliang (American Physiological Society, 2013)
The related transcriptional enhancer factor-1 (RTEF-1) increases gene transcription of hypoxia-inducible factor 1α (HIF-1α) and enhances angiogenesis in endothelium. Both hypoxia and inflammatory factor TNF-α regulate gene expression of HIF-1α, but how RTEF-1 and TNF-α coordinately regulate HIF-1α gene transcription is unclear. Here, we found that RTEF-1 interacts with p65 subunit of NF-κB, a primary mediator of TNF-α. RTEF-1 increased HIF-1α promoter activity, whereas expression of p65 subunit inhibited the stimulatory effect. By contrast, knockdown of p65 markedly enhanced RTEF-1 stimulation on the HIF-1α promoter activity (7-fold). A physical interaction between RTEF-1 and p65 was confirmed by coimmunoprecipitation experiments in cells and glutathione S-transferase (GST)-pull-down assays. A computational analysis of RTEF-1 crystal structures revealed that a conserved surface of RTEF-1 potentially interacts with p65 via four amino acid residues located at T347, Y349, R351, and Y352. We performed site-directed mutagenesis and GST-pull-down assays and demonstrated that Tyr352 (Y352) in RTEF-1 is a key site for the formation of RTEF-1 and p65-NF-κB complex. An alanine mutation at Y352 of RTEF-1 disrupted the interaction of RTEF-1 with p65. Moreover, expression of RTEF-1 decreased TNF-α-induced HIF-1α promoter activity, IL-1β, and IL-6 mRNA levels in cells; however, the effect of RTEF-1 was largely lost when Y352 was mutated to alanine. These results indicate that RTEF-1 interacts with p65-NF-κB through Y352 and that they antagonize each other for HIF-1α transcriptional activation, suggesting a novel mechanism by which RTEF-1 regulates gene expression, linking hypoxia to inflammation.